Means to an End : U.S. Interest in the International Criminal Court - Feinstein, Lee; Lindberg, Tod (Book collections on Project MUSE., 2009)
"Reassesses U.S. relationship with the ICC and broader issues of U.S. policy toward international justice. Argues U.S. active support of ICC serves U.S. interests and is consistent with values to which America has aspired. Focuses on foreign policy, national security, and moral cases for shifting U.S. policy toward the Court"--Provided by publisher